Analysis of Regional Tax Revenue Performance Measurement on Regional Original Income of Magetan District and Gresik District, 2018-2021 - Mukti Prasaja (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
This study aims to identify, explain and compare regional tax revenues for Magetan and Gresik Regencies through an analysis of effectiveness, efficiency, contribution, optimization and growth rate for 2018-2021. The data used is secondary data, namely the 2018-2021 Magetan and Gresik Regency Budget Realization Reports. Data collection technique is a method of documentation. The analysis technique used is a quantitative descriptive method. The results of this study are (1) During 2018-2021, the average level of effectiveness for Magetan Regency and Gresik Regency is very effective. The average efficiency level for Magetan Regency and Gresik Regency is very efficient. The average contribution level for Magetan Regency is in the medium criteria, while Gresik Regency is in the very good criteria. The average level of optimization for Magetan Regency and Gresik Regency is included in the optimal criteria. The average growth rate for Magetan and Gresik districts is included in the criteria of not being successful. (2) Gresik Regency Regional Tax Revenue has better revenue performance than Magetan Regency Regional Tax Revenue performance.